Digital transformation of the interior design industry: selected case studies from South Africa, China and Canada - Xiao, Jun Zhou (My University, 2021)
In the context of the fourth Industrial Revolution, a series of digital technologies were derived. The emergence of these digital technologies has greatly promoted the industry's reform and innovation, among which the interior design industry is one. This paper mainly discusses the digital transformation of the interior design industry and studies the influence of digital technology on the operation of interior design enterprises, core design process, interior design products and users during the transformation process. This study is based on the feedback of interior design companies, designers and users in South Africa, Canada and China. By selecting different research objects of different digital infrastructure level, this study explores the role and effectiveness of digital technology in the process of the digital transformation of the interior design industry. By comparing the comprehensive data of different countries, this paper makes a comprehensive analysis of the interior design industry from the perspective of the digital transformation of interior design enterprises, core digital design process and interior design products and services to explore the importance and inevitability of digital transformation
A research report submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Management in the field of Digital Business, 2021
Keywords: Digital Technology; Digital Transformation; Interior Design; SDG-9: Industry, innovation and infrastructure; SDG-8: Decent work and economic growth